2005
DOI: 10.1016/j.otohns.2004.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth and telomerase activity by novel cationic ceramide analogs with high solubility in human head and neck squamous cell carcinoma cells

Abstract: These data suggest that the novel C6-Pyr-Cer with high solubility and bioavailability may lead to the development of new therapeutic strategies that target telomerase for the treatment of HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 16 publications
4
40
0
Order By: Relevance
“…This synergistic action was also evident in an overadditive increase of caspase-3 and caspase-9 activity and the number of cells with dissipated Dc m , suggesting mitochondria to be a target of doxorubicin in SW403 cells. This phenomenon has also been recently described using short-chain pyridinium ceramides and doxorubicin in HepG2 cells (53). However, in our hands, doxorubicin did not induce any alteration in endogenous ceramide levels in the cellular fractions analyzed (mitochondrial, cytosolic, and extramitochondrial).…”
Section: Discussionsupporting
confidence: 89%
“…This synergistic action was also evident in an overadditive increase of caspase-3 and caspase-9 activity and the number of cells with dissipated Dc m , suggesting mitochondria to be a target of doxorubicin in SW403 cells. This phenomenon has also been recently described using short-chain pyridinium ceramides and doxorubicin in HepG2 cells (53). However, in our hands, doxorubicin did not induce any alteration in endogenous ceramide levels in the cellular fractions analyzed (mitochondrial, cytosolic, and extramitochondrial).…”
Section: Discussionsupporting
confidence: 89%
“…The accumulation of D-erythro-C 6 -Pyr-Cer specifically in mitochondria has been confirmed recently, and the data showed that mitochondrial localization of Pyr-Cer caused a decrease in its membrane potential, leading to cytochrome C release and apoptosis (Novgorodov et al, 2005). In another independent study, antiproliferative responses of L-t-C 6 -Pyr-Cer, such as inhibition of cell cycle and telomerase activity, in HNSCC cell lines, but not in noncancerous human adult keratinocytes and Wi-38 lung fibroblasts, were demonstrated (Rossi et al, 2005). The improved effects of L-t-C 6 -Pyr-Cer in combination with gemcitabine (GMZ) in the inhibition of cell growth were also shown in HNSCC cells in vitro (Rossi et al, 2005).…”
mentioning
confidence: 76%
“…To overcome these problems, many biophysical and chemical approaches have been developed with improved delivery and bioavailability (Shabbits and Mayer, 2003;Stover and Kester, 2003). Another alternative approach has been the development of novel pyridinium ceramide analogs with increased water solubility, cell membrane permeability, and cellular uptake compared with their uncharged conventional ceramides (Novgorodov et al, 2005;Rossi et al, 2005). Pyridinium ceramides are designed to preferentially localize into negatively charged intracellular compartments, specifically mitochondria and nucleus, due to the presence of a positive charge delocalized over the -electron system.…”
mentioning
confidence: 99%
“…After 24 h, cells were incubated with different concentrations of C 6 -pyridinium ceramide or C 6 -ceramide for specifi ed times. The IC 50 of each compound was determined from cell growth plots ( 26 ). For Trypan blue exclusion assay, MCF7 cells were plated onto 6-well plates (1 × 10 5 cells/plate) and then treated with 10 M C 6 -pyridinium ceramide or C 6 -ceramide for specifi ed times.…”
Section: Mtt and Trypan Blue Exclusion Assaysmentioning
confidence: 99%